Adenosine A2A Receptor: A New Neuroprotective Target in Light-Induced Retinal Degeneration - Soliño, Manuel; Larrayoz, Ignacio M.; López, Ester María; Rey-Funes, Manuel; Bareiro, Mariana; Loidl, Cesar Fabián; Girardi, Elena; Martínez, Alfredo; López-Costa, Juan José (Frontiers in Pharmacology, 2022)
ABSTRACT Continuous illumination induces the degeneration of photoreceptors. This animal model of light induced retinal degeneration (LIRD) resembles many characteristics of human degenerative diseases of the outer retina as Age-related Macular Degeneration (AMD). The aim of this work was to evaluate the potential neuroprotective effect of the modulation of adenosine A2A receptor in the model of LIRD. Sprague Dawley rats were intravitreally injected in the right eye with either CGS 21680 (A2AR agonist) or SCH 58261 (A2AR antagonist). Contralateral eyes were injected with respective vehicles as control. Then, rats were subjected to continuous illumination (12,000 lux) for 24h. Retinas were processed by GFAP immunohistochemistry (IHC), TUNEL technique, Western blotting (WB) and qRT-PCR. Another group of rats was subjected to functional studies by electroretinography (ERG). Animals treated with CGS21680 showed a significant increase of apoptotic nuclei in outer nuclear layer (ONL) and a significant increase of GFAP immunoreactive area of the retinas, but did not alter WB and ERG results. qRT-PCR revealed that CGS 21680 significantly increased the expression of IL1β . On the opposite, SCH 58261 significantly decreased apoptotic nuclei in ONL and GFAP immunoreactive area of the retinas. It also significantly decreased GFAP and activated Caspase-3 levels in WB, and preserved retinal function since treated eyes showed significantly greater amplitudes of a-, b-waves, and oscillatory potentials. qRT-PCR revealed that SCH 58261 significantly decreased the expression of TNFα. These results show that the blockage of A2AR before the start of the pathogenic process is neuroprotective as it prevents light induced retinal damage. The use of A2A receptor antagonists deserves to be evaluated in retinal degenerative diseases.